2010
DOI: 10.1590/s0004-27492010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Ability of corneal biomechanical metrics and anterior segment data in the differentiation of keratoconus and healthy corneas

Abstract: Purpose: To evaluate the sensitivity, specificity, and test accuracy of corneal biomechanical metrics and anterior segment data in differentiating keratoconus from healthy corneas. Methods: Comparative case series. Patients with and without keratoconus (gender and age-matched) were submitted for complete eye examinations including corneal hysteresis (CH) and corneal resistance factor (CRF) as measured by the Ocular Response Analyzer and anterior segment data as gathered through Pentacam assessments. The anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 34 publications
(45 reference statements)
2
20
1
1
Order By: Relevance
“…The timing of the spikes indicates when the applanation events occurred within the 25-millisecond measurement (24) . The ORA pressure parameters had significantly lower mean values in keratoconus compared to normal eyes, supporting the results of previous studies (25)(26) . CH, CRF, and IOPg exhibited significantly different distributions in normal and keratoconic eyes (Mann-Whitney U-test, p<0.0001) in the analysis of the waveform signal and mean of consecutive measurements.…”
Section: Discussionsupporting
confidence: 90%
“…The timing of the spikes indicates when the applanation events occurred within the 25-millisecond measurement (24) . The ORA pressure parameters had significantly lower mean values in keratoconus compared to normal eyes, supporting the results of previous studies (25)(26) . CH, CRF, and IOPg exhibited significantly different distributions in normal and keratoconic eyes (Mann-Whitney U-test, p<0.0001) in the analysis of the waveform signal and mean of consecutive measurements.…”
Section: Discussionsupporting
confidence: 90%
“…5 Therefore, for corneas with keratoconus, lower values were found for most parameters. 3,14,15 However, our data showed that some parameters derived from the waveform signal; i.e. path 1, 2, 11, 21 and aplhf, were higher in patients with keratoconus.…”
Section: Discussioncontrasting
confidence: 59%
“…Corneal hysteresis (CH) and the corneal resistance factor (CRF), which are the corneal biomechanical metrics generated by the ORA, have been the subjects of several recent publications. 3,4 Luce presented data (Luce D, ORA waveform analysis and beyond. Presented at: American Society of Cataract and Refractive Surgery Annual Meeting, April 3 to 8,2009; San Francisco, California) indicating that waveform parameters provided from the ORA signal may be more sensitive than CH or the CRF in discriminating abnormal corneas.…”
Section: 5005/jp-journals-10025-1028mentioning
confidence: 99%
“…Other hopeful but as yet unvalidated techniques include biomechanical characterization using the Ocular Response Analyzer (Reichert, Buffalo, NY), which, although theoretically promising, 10 has demonstrated limited ability in screening for ectatic diseases, 29,30 and the recently FDA-approved Oculus Corvis ST. 31 Ambrósio & Randleman/Editorial SUMMARY: SCREENING TODAY So, what should we be using to screen our patients in 2013? Well-established Placido-based criteria remain an integral part of screening until this is defi nitively surpassed by other technology.…”
Section: Additional Screening Toolsmentioning
confidence: 99%